PERBANDINGAN PERTUMBUHAN EKSPLAN PADA PENGGUNAAN AIR LIMBAH AC (AIR CONDITONER) DENGAN AKUADES DALAM MEDIA SUBKULTUR DURIAN LAHUNG (Durio dulcis) - Sriana, Hemy; Farah, Sarifah Noor (Universitas Lambung Mangkurat, 2023)
Durian lahung (Durio dulcis) is one of the germplasm of Kalimantan which is becoming rare. One method of propagation with the advantage of obtaining lots of seeds, simultaneously and free from pests is through in vitro technique. One of the obstacles encountered in this process in the laboratory is the use of large amounts of aquades (distilled water), so alternative water is needed with almost the same characteristics so that it does not interfere the growth of explants, namely AC wastewater. The aim of this research is to compare the growth results of Lahung durian explants in a second subculture medium using AC wastewater which is unused waste with distilled water. The experimental design uses the t test by comparing 2 independent populations. The sample consists of a population from subculture result on media with an AC wastewater source and a population on distilled water. Each population consists of 10 replications and each replication consists of 5 bottles, so there are 100 planting bottles. The observations were made on the variables of contamination percentage (%), life percentage (%), browning percentage (%), number of roots, number of shoots, number of leaves, number of plumules, and shoot height. The results of the observations at 6 weeks after subculture showed that the explants from both treatments did not experience contamination, browning, and root growth, and 100% of the explants were alive. Meanwhile, the number of leaves, the number of plumules, shoots, nodes and shoot height were not significantly different between the two treatments.